Hitchhiking vesicular transport routes to the vacuole: amyloid recruitment to the Insoluble Protein Deposit (IPOD) - Kumar, Rajesh; Neuser, Nicole; Tyedmers, Jens (Prion, 2017)
Sequestration of aggregates into specialized deposition sites occurs in many species across all kingdoms of life ranging from bacteria to mammals and is commonly believed to have a cytoprotective function. Yeast cells possess at least 3 different spatially separated deposition sites, one of which is termed “Insoluble Protein Deposit (IPOD)” and harbors amyloid aggregates. We have recently discovered that recruitment of amyloid aggregates to the IPOD uses an actin cable based recruitment machinery that also involves vesicular transport.1 Here we discuss how different proteins known to be involved in vesicular transport processes to the vacuole might act to guide amyloid aggregates to the IPOD. These factors include the Myosin V motor protein Myo2 involved in transporting vacuolar vesicles along actin cables, the transmembrane protein Atg9 involved in the recruitment of large precursor hydrolase complexes to the vacuole, the phosphatidylinositol/ phosphatidylcholine (PI/PC) transfer protein Sec 14 and the SNARE chaperone Sec 18. Furthermore, we present new data suggesting that the yeast dynamin homolog Vps1 is also crucial for faithful delivery of the amyloid model protein PrD-GFP to the IPOD. This is in agreement with a previously identified role for Vps1 in recruitment of heat-denatured aggregates to a perivacuolar deposition site.
Gesehen am 09.11.2018